Analysis of Integration Tri Hita Karana Values in the Philosophy of Maja Labo Dahu and Ngaha Aina Ngoho as a Model for Strengthening Cultural Literacy in Bima Young Generation - Ita Fitriati; I Made Tegeh; I Wayan Santyasa (Yayasan Insan Mulia Bima, 2026)
This study analyzes the integration of Tri Hita Karana (THK) values with the core philosophies of the Bima community Maja Labo Dahu and Ngaha Aina Ngoho a model for strengthening cultural literacy among the younger generation of Bima. The THK principles of harmony with God (Parahyangan), fellow humans (Pawongan), and nature (Palemahan) are philosophically aligned with Bima’s moral and ethical values. Using a descriptive-exploratory qualitative approach, data were collected through in-depth interviews, observations, and documentation, and analyzed thematically through data reduction, categorization, and hermeneutic interpretation. The findings show that Maja Labo Dahu aligns with Parahyangan and Pawongan through moral awareness and social ethics, while Ngaha Aina Ngoho relates to Pawongan and Palemahan by emphasizing independence, responsibility, and cultural sustainability. This integration forms a culturally relevant model for strengthening youth cultural literacy amid social change, modernization, and global challenges